Adverse effects of adjuvant endocrine therapy - E. I. Kovalenko; I. B. Kononenko; A. V. Snegovoi; O. P. Grebennikova; L. V. Manzyuk (Медицинский совет, 2018)
Hormonal therapy is a highly effective and well tolerable treatment of hormone-responsive breast cancer. However, it has some side effects that can affect quality of life and lead to treatment discontinuation. Common side effects of tamoxifen and aromatase inhibitors are discussed in this article: menopausal, gynecological symptoms, cardiovascular and musculoskeletal adverse events. Some of them are preventable and manageable. In order to maintain good quality of life during treatment the oncologists should pay more attention to the side effects that lead to it’s deterioration and not be too anxious about insignificant ones.